On the value of the Digital Internet / Physical Internet analogy - van Luik, Sharon; Fiebig, Tobias; Fahim, Patrick; de Waard, Pieter; Tavasszy, Lorant (Journal of Supply Chain Management Science, 2020)
Classical logistic networks have long since struggled with the increasing demand for flexibility and responsiveness, driven by the emancipation of consumers and the globalization of our world. Hence, since 2010, researchers in the logistics domain propose the ‘Physical Internet’ (PI) as guiding vision for innovations in logistic networks. The PI model adopts concepts and ideas from the ‘Digital Internet’ (DI) world and applies these to the movement and storage of physical products. While researchers have been working with this analogy for the past decade, a debate has emerged about the value of the DI/PI analogy and its usefulness for guiding the design of the PI. Specifically, prior work has not focused on ascertaining the accuracy of the analogy, i.e., how well logistics researchers have adopted concepts from the Digital Internet, and how this may influence the value of the analogy in the current discourse. The aim of this paper is to help fill this gap, using a qualitative research approach. We use 15 semi-structured expert interviews, to determine how well the DI is understood among the experts working on the DI/PI analogy. We propose the Analogy Functionality Model to interpret the results and assess the current strength of the analogy. We find that the strength of the DI/PI analogy varies across functions. Its application value lies particularly in the persuasion of stakeholders, the accessible explanation of key concepts, and the gathering of inspiration for further design directions. This underlines the importance of the analogy for the PI innovation community. Researchers and logistics practitioners should, however, refrain from using the analogy as a blueprint for the design of PI systems. For implementation purposes, we recommend that researchers move to conceptually emancipate the PI from the DI.